Several Problems in Particle Physics and Cosmology Solved in One SMASH - Ballesteros, Guillermo; Redondo, Javier; Ringwald, Andreas; Tamarit, Carlos (Frontiers in Astronomy and Space Sciences, 2019)
The Standard Model (SM) of particle physics is a big success. However, it lacks explanations for cosmic inflation, the matter-anti-matter asymmetry of the Universe, dark matter, neutrino oscillations, and the feebleness of CP violation in the strong interactions. The latter may be explained by introducing an exotic vector-like quark which is charged under a chiral global U(1) Peccei-Quinn (PQ) symmetry which is spontaneously broken by the vacuum expectation value of a complex SM singlet scalar field—the PQ field. Moreover, the pseudo Nambu-Goldstone boson of this breaking—the axion—may play the role of the dark matter. Furthermore, the modulus of the PQ field is a candidate for driving inflation. Furthermore, three extra SM singlet neutrinos are added who acquire their Majorana mass from the breaking of the PQ symmetry and which explain the small masses of the active neutrinos and their oscillations by the seesaw mechanism. The resulting extension of the SM which has been dubbed SMASH—for SM-Axion-Seesaw-Higgs portal inflation—solves the five aforementioned problems in one stroke. We review how this works in SMASH and discuss its further predictions and tests in astrophysics, cosmology, and laboratory experiments. Furthermore, we consider and comment on variants of SMASH.